Novel oral SPT inhibitor CH5169356 inhibits hepatic stellate cell activation and ameliorates hepatic fibrosis in mouse models of non‐alcoholic steatohepatitis (NASH) - Natsuko Hada; Asao Katsume; Kawasaki Kenichi; Chihiro Endo; Naoshi Horiba; Masayuki Sudoh (Wiley, 2023)
Abstract Ceramide is a central molecule of sphingolipid metabolism and is involved in the development of non‐alcoholic fatty liver disease (NAFLD) and non‐alcoholic steatohepatitis (NASH). It has already been reported that the inhibition of serine palmitoyltransferase (SPT), the rate‐limiting enzyme in the sphingolipid biosynthetic pathway, has an inhibitory effect on hepatic lipidosis, but its effect on severe hepatic fibrosis is not clear. In this study, we examined whether a SPT inhibitor could suppress the activation of hepatic stellate cells (HSC) and ameliorate the progression of NASH. Effects on sphingolipid metabolism and HSC activation marker genes by NA808, a SPT inhibitor, were evaluated in an immortalized HSC cell line (E14C12). NA808 decreased sphingolipid synthesis and the expression of α‐smooth muscle actin (α‐SMA) and collagen 1A1 mRNA in HSC. We identified a novel oral SPT inhibitor, CH5169356, which is a prodrug of NA808. CH5169356 was administered in the Ath+HF model, a NASH mouse model with liver fibrosis induced by atherogenic and high‐fat content diets. CH5169356 showed a significant decrease in the expression of α‐SMA and collagen 1A1 mRNA in the liver and an inhibition of liver fibrosis progression. CH5169356 was also evaluated in a Stelic animal model (STAM), a NASH mouse model induced through a different mechanism than that of the Ath+HF model, and showed a significant anti‐fibrotic effect. In conclusion, CH5169356 could inhibit the progression of hepatic fibrosis in the pathogenesis of NASH by suppressing HSC activation, suggesting that CH5169356 would be a potential oral NASH therapeutic agent.